Built environment and physical activity in New Zealand adolescents: a protocol for a cross-sectional study. Issue 4 (15th April 2014) - Hinckson, Erica A; Duncan, Scott; Oliver, Melody; Mavoa, Suzanne; Cerin, Ester; Badland, Hannah; Stewart, Tom; Ivory, Vivienne; McPhee, Julia; Schofield, Grant
Abstract : Introduction: Built-environment interventions have the potential to provide population-wide effects and the means for a sustained effect on behaviour change. Population-wide effects for adult physical activity have been shown with selected built environment attributes; however, the association between the built environment and adolescent health behaviours is less clear. This New Zealand study is part of an international project across 10 countries (International Physical Activity and the Environment Network–adolescents) that aims to characterise the links between built environment and adolescent health outcomes. Methods and analyses: An observational, cross-sectional study of the associations between measures of the built environment with physical activity, sedentary behaviour, body size and social connectedness in 1600 New Zealand adolescents aged 12–18 years will be conducted in 2013–2014. Walkability and neighbourhood destination accessibility indices will be objectively measured using Geographic Information Systems (GIS). Physical activity and sedentary behaviours will be objectively measured using accelerometers over seven consecutive days. Body mass index will be calculated as weight divided by squared height. Demographics, socioeconomic status, active commuting behaviours and perceived neighbourhood walkability will be assessed using the Neighbourhood Environment Walkability Scale for Youth and psychosocial indicators. A web-based computer-assisted personal interview tool Visualisation and Evaluation of Route Itineraries, Travel Destinations, and Activity Spaces (VERITAS) and Global Positioning System (GPS) receivers will be used in a subsample of 300 participants. A qualitative research component will explore barriers and facilitators for physical activity in adolescents with respect to the built and social environment in a subsample of 80 participants. Ethics and dissemination: The study received ethical approval from the Auckland University of Technology Ethics Committee (12/161). Data will be entered and stored into a secure (password protected) database. Only the named researchers will have access to the data. Data will be stored for 10 years and permanently destroyed thereafter. The results papers will be submitted for publication in peer-reviewed journals.